2003
DOI: 10.1055/s-2003-41624
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Tumour Necrosis Factor-α Receptor I and Interleukin-6 as Markers of Activity in Thyrotoxic Graves' Disease

Abstract: Autoimmune thyroid diseases are thought to be mediated by pro-inflammatory cytokines such as TNFalpha and IL-6. Serum levels of cytokines may indicate activity levels of immune functions. We investigated serum levels of IL-6 and of the soluble receptor of TNFalpha in patients with newly diagnosed onset of Graves' hyperthyroidism. The predominantly female group consisted of 39 patients, mean fT4 was 47.6 pg/ml (normal values 7.5=19.0 pg/ml). After diagnosis, all patients were treated with anti-thyroid drugs. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Reuter et al . showed a significant correlation between elevated sTNF-R1 levels and increased levels of FT4, FT3, TRAb and thyroidal Tc-99m uptake in 39 hyperthyroid patients ( 29 ). Similar findings were reported by Díez et al .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Reuter et al . showed a significant correlation between elevated sTNF-R1 levels and increased levels of FT4, FT3, TRAb and thyroidal Tc-99m uptake in 39 hyperthyroid patients ( 29 ). Similar findings were reported by Díez et al .…”
Section: Resultsmentioning
confidence: 98%
“…Only a few studies have included the measurements of serum levels of soluble cytokine receptors such as sTNF-R1 ( 2 , 26 , 27 , 28 , 29 ) and sTNF-R2 ( 30 ). Reuter et al .…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated that serum TNF-α levels are elevated in patients with TAO, but not in those with GD without TAO [37]. Serum TNF-α and soluble TNF receptor levels are elevated in patients with newly diagnosed GD, and decrease following correction of hyperthyroidism [40]. Gene polymorphism analyses have demonstrated that single nucleotide polymorphisms (SNPs) of the TNF-α gene are associated with TAO in Japanese and Iranian populations [41, 42].…”
Section: Cytokine Pathways Potentially Relevant To Taomentioning
confidence: 99%